An Update of Fungal Endophyte Diversity and Strategies for Augmenting Therapeutic Potential of their Potent Metabolites: Recent Advancement - Prajapati C.; Rai S.N.; Singh A.K.; Chopade B.A.; Singh Y.; Singh S.K.; Haque S.; Prieto M.A.; Ashraf G.M. (My University, 2025)
Endophytic fungi represent a significant renewable resource for the discovery of pharmaceutically important compounds, offering substantial potential for new drug development. Their ability to address the growing issue of drug resistance has drawn attention from researchers seeking novel, nature-derived lead molecules that can be produced on a large scale to meet global demand. Recent advancements in genomics, metabolomics, bioinformatics, and improved cultivation techniques have significantly aided the identification and characterization of fungal endophytes and their metabolites. Current estimates suggest there are approximately 1.20 million fungal endophytes globally, yet only around 16% (190,000) have been identified and studied in detail. This underscores the vast untapped potential of fungal endophytes in pharmaceutical research. Research has increasingly focused on the transformation of bioactive compounds by fungal endophytes through chemical and enzymatic processes. A notable example is the anthraquinone derivative 6-O-methylalaternin, whose cytotoxic potential is enhanced by the addition of a hydroxyl group, sharing structural similarities with its parent compound macrosporin. These structure-bioactivity studies open up new avenues for developing safer and more effective therapeutic agents by synthesizing targeted derivatives. Despite the immense promise, challenges remain, particularly in the large-scale cultivation of fungal endophytes and in understanding the complexities of their biosynthetic pathways. Additionally, the genetic manipulation of endophytes for optimized metabolite production is still in its infancy. Future research should aim to overcome these limitations by focusing on more efficient cultivation methods and deeper exploration of fungal endophytes’ genetic and metabolic capabilities to fully harness their therapeutic potential. © The Author(s) 2025.